Metabolic trade-offs favor regulated hypothermia and inhibit fever in immune-challenged chicks - do Amaral-Silva, Lara [UNESP]; da Silva, Welex Cândido [UNESP]; Gargaglioni, Luciane Helena [UNESP]; Bícego, Kênia Cardoso [UNESP] (The Company of Biologists, 2022)
The febrile response to resist a pathogen is energetically expensive, while regulated hypothermia seems to preserve energy for vital functions. We hypothesized here that immune-challenged birds facing metabolic trade-offs (reduced energy supply/increased energy demand) favor a regulated hypothermic response at the expense of fever. To test this hypothesis, we compared 5 day old broiler chicks exposed to fasting, cold (25°C), and fasting combined with cold with a control group fed under thermoneutral conditions (30°C). The chicks were injected with saline or with a high dose of endotoxin known to induce a biphasic thermal response composed of a drop in body temperature (Tb) followed by fever. Then Tb, oxygen consumption (metabolic rate), peripheral vasomotion (cutaneous heat exchange), breathing frequency (respiratory heat exchange) and huddling behavior (heat conservation indicator) were analyzed. Irrespective of metabolic trade-offs, chicks presented a transient regulated hypothermia in the first hour, which relied on a suppressed metabolic rate for all groups, increased breathing frequency for chicks fed/fasted at 30°C, and peripheral vasodilation in chicks fed/fasted at 25°C. Fever was observed only in chicks kept at thermoneutrality and was supported by peripheral vasoconstriction and huddling behavior. Fed and fasted chicks at 25°C completely eliminated fever despite the ability to increase metabolic rate for thermogenesis in the phase correspondent to fever when it was pharmacologically induced by 2,4-dinitrophenol. Our data suggest that increased competing demands affect chicks' response to an immune challenge, favoring regulated hypothermia to preserve energy while the high costs of fever to resist a pathogen are avoided.
Keywords: Birds; Cold; Endotoxin; Fasting; Fever; Regulated hypothermia